Childhood cancer incidence and survival in Thailand: A comprehensive population‐based registry analysis, 1990–2011. Issue 1 (31st August 2018) - Bidwell, Serena S.; Peterson, Catherine C.; Demanelis, Kathryn; Zarins, Katie R.; Meza, Rafael; Sriplung, Hutcha; Wiangnon, Surapon; Chotsampancharoen, Thirachit; Chitapanarux, Imjai; Pongnikorn, Donsuk; Daoprasert, Karnchana; Suwanrungruang, Krittika; et al.
Abstract: Background: Southeast Asia is undergoing a transition from infectious to chronic diseases, including a dramatic increase in adult cancers. Childhood cancer research in Thailand has focused predominantly on leukemias and lymphomas or only examined children for a short period of time. This comprehensive multisite study examined childhood cancer incidence and survival rates in Thailand across all International Classification of Childhood Cancer (ICCC) groups over a 20‐year period. Methods: Cancer cases diagnosed in children ages 0‐19 years ( n  = 3574) from 1990 to 2011 were extracted from five provincial population‐based Thai registries, covering approximately 10% of the population. Descriptive statistics of the quality of the registries were evaluated. Age‐standardized incidence rates (ASRs) were calculated using the Segi world standard population, and relative survival was computed using the Kaplan‐Meier method. Changes in incidence and survival were analyzed using Joinpoint Regression and reported as annual percent changes (APC). Results: The ASR of all childhood cancers during the study period was 98.5 per million person‐years with 91.0 per million person‐years in 1990–2000 and 106.2 per million person‐years in 2001–2011. Incidence of all childhood cancers increased significantly (APC = 1.2%, P  < 0.01). The top three cancer groups were leukemias, brain tumors, and lymphomas. The 5‐year survival for all childhood cancers significantly improved from 39.4% in 1990–2000 to 47.2% in 2001–2011 ( P  < 0.01). Conclusions: Both childhood cancer incidence and survival rates have increased, suggesting improvement in the health care system as more cases are identified and treated. Analyzing childhood cancer trends in low‐ and middle‐income countries can improve understanding of cancer etiology and pediatric health care disparities.